An Investigation of the Relationship between Involvement Sites in Vitiligo Patients and Autoimmune Diseases and Hematological Parameters - KARAGUN, Ebru (International Journal of Innovative Research in Medical Science, 2019)
Aim-Objectives: Vitiligo is an acquired idiopathic disease which progresses with melanocyte destruction and is clinically characterized by depigmented lesions of unknown etiology. Vitiligo may be coexistence with a autoimmune and endocrine disorders. This study examined the sT3, fT4, TSH, Anti-TPO, Anti-Tg, Vitamin B12 and fasting blood glucose (FBG) values, and thrombocyte-to-lymphocyte ratio(TLR), neutrophil-to-lymphocyte ratio(NLR), the mean platelet volume(MPV) the correlation of depigmented lesions with the extent of body involvement sites(IS). Materials and Method: The study enrolled 67 patients aged 0‒65 who were diagnosed with non-segmental generalized vitiligo and in whom an increase in lesions had been observed in the last six months. The IS of the lesions in the patients were evaluated as IS ˂10%(1st group), 10%‒20% (2nd group), 20% - 30%(3rd group), 30% - 40%(4th group), 40% ‒50 %(5th group), and ˃50%(6th group). The control group consisted of patients who had presented to the outpatient clinic having had no history of vitiligo detected in themselves nor in their families. Results: No significant correlation was found between IS and sT3, fT4, TSH, Anti-TPO, Anti-Tg, Vit. B12, PBG or MPV. A moderately positive correlation was found between IS and duration (p <0.05) and a mildly positive correlation between IS and NLR and TLR (p <0.05). Conclusion: This study show that every patient diagnosed with vitiligo, independent of the IS, should undergo examination for autoimmune disease. A mild positive correlation between VTA and NLO-TLO was found to be an indicator of increased inflammation in vitiligo patients as the extent of lesions increased.